Regions on plasmid pCU1 required for the killing of Klebsiella pneumoniae. - Thatte, V (1985)
Plasmid pCU1 was Kik+ (promotes killing of Klebsiella pneumoniae). All Tn5 insertions within the tra region of pCU1 were Kik-. Two other regions, kikA and kikB, were needed. They may be separated on different plasmids, but both must be mobilized into Klebsiella pneumoniae. Establishment of one kik region in K. pneumoniae followed by receipt of the second did not lead to killing. Kik was therefore intracellular and required concerted and transient action of both regions.